A randomised trial to evaluate the effectiveness of an Islamic psychospiritual ACT-based prevention program for at-risk young adults during the COVID-19 pandemic - Abdul Khaiyom, Jamilah Hanum; Abdul Aziz, Amani Fadzlina; Md Rosli, Ahmad Nabil; Bahari, Che Amnah; Abdullah, Nur Sakinah Thomas (2021)
Objective: With rising psychological concerns amidst the pandemic, efforts are needed to preserve the mental health of at-risk populations. The present study examined the effectiveness of i-ACT for LifeTM, an Islamic psychospiritual Acceptance and Commitment Therapy-based prevention program to reduce psychological distress in at-risk young adults in Malaysia during the COVID-19 pandemic. Method: The study was preregistered at ClinicalTrials.gov (NCT04870385). Purposive sampling was used to recruit university students studying in Malaysia (n=93, 78% female) aged 18-29 years old. The adapted WHO ACT-based module with the elements of Islamic spirituality was used. The prevention program consists of five weekly modules (Grounding, Unhooking, Acting on Values, Being Kind, and Making Room). Each corresponded to an ACT core process and was supplemented with Qur’ānic verses, Hadīth, religious/spiritual activities, and spiritual-relevant poems. The program was designed for delivery through web-based instant messaging platforms. Participants were randomized to either receive the prevention program (n=46) or be waitlisted (n=47), and were asked to complete assessments at pre-intervention, mid-intervention, post-intervention, and 1-month follow-up. The outcome assessed were anxiety, stress, depression, self-compassion, psychological flexibility, and resilience. Results: Intention-to-treat analyses using Last Observation Carried Forward reported significant between-group effects at post-intervention and follow-up (p<.05), and a significant overall effect of time across the four-time points (p<.001), for all the outcome measures. Observations on participants' reflections of the Islamic spirituality elements are generally positive. Conclusions: Findings suggest that the i-ACT for LifeTM web-based prevention programs effectively preserve the mental health of Muslim young adults in Malaysia during the pandemic. The program was also found to support the integration of Islamic spiritual elements into traditional cognitive-behavioural and mindfulness techniques in improving the acceptability of mental health interventions. Future studies are encouraged to examine the module's effectiveness among different populations.